Learning through intuitive interface: A case study on preschool learning. (November 2018) - Lai, Ngan Kuen; Ang, Tan Fong; Por, Lip Yee; Liew, Chee Sun
Abstract: For a child, playing is not only an act of fun, but also a way of learning. Long hours of study in a classroom without playing only serve to make the children detest learning. A current interest of research is to integrate the learning process with the latest technology to engage children with learning and playing. Game-based learning (GBL) is one of the approaches that utilises the gaming environment to attract the student's attention and increase participation throughout the process of learning. We proposed an intervention program that used voice and gesture-based interactive virtual learning environment (VGVLE) based on GBL framework to teach colour and shape to preschool children. The program with quasi-experimental design (N = 84) was conducted to evaluate the effectiveness of the proposed approach in promoting preschool learning when compared with the traditional classroom teaching approach. Our findings show that pre-schoolers who learnt with the proposed approach surpassed those who learnt with the classroom approach. Besides that, the gap in learning performance was also reduced. Highlights: We proposed voice and gesture-based interaction (VGVLE) for preschool learning. VGVLE deepens their understanding and memory of learning materials. VGVLE enhances the children's learning experience and performance. The children's learning performance gap was reduced. Games can be used as one of the formal assessment approaches especially for preschool children.